Cleaner production mechanism: The reuse of sewage in mining - Vera Torrejón, José Antonio (2016)
The cleaner production mechanisms are based on principles of prevention and sustainable development, which objectives are to protect the environment -through conservation or sustainable use of natural resources- and to preserve environmental quality. As one of the mechanisms for cleaner production in water resources management, the author defines and develops the concept of wastewater reuse, emphasizing its application on mining. Finally, some reuse of wastewater experiences applied by mining companies are presented.